The Influence of Halal Labels , Brand Image, and Consumer Animosity on Gen Z Muslim Consumers' Purchase Intention on the Issue of Boycotting Citra Body Lotion Products - Qonita Rahma Humairo; Nurwinsyah Rohmaningtyas; Anees El Zer (International Conference on Islamic Economic (ICIE), 2026)
This study aims to determine the effect of Halal Label, Brand Image and Consumer Animosity on the Purchase Intention of Citra Body Lotion which is experiencing a boycott issue among Gen Z Muslims in Surabaya using quantitative methods from primary data obtained through online questionnaires. The sampling technique used was purposive sampling with a total of 140 respondents. Respondents selected in this study were Gen Z Muslims who live in Surabaya City. Data analysis was carried out using Statistical Product and Service Solutions (SPSS). The results of the study indicate that partially the halal label has a significant positive effect on the purchase intention of Citra Body Lotion, Brand Image has a significant positive effect on the purchase intention of Citra Body Lotion and Consumer Animosity also has a significant negative effect on the purchase intention of Citra Body Lotion, which indicates that consumer sentiment or emotional attitudes towards certain issues can influence their purchase intentions. Simultaneously, the halal label, Brand Image and Consumer Animosity have a significant effect on the purchase intention of Citra Body Lotion. This research contributes to the understanding of Muslim consumer behavior, especially from Generation Z in responding to the issue of product boycotts and provides practical implications for companies in understanding purchasing intention through Halal Labels , Brand Image and Consumer Animosity.